UNDERSTANDING IN HERMENEUTICS AND POETIC SPEECH - Musa Tadjibaev (International Journal of Literature and Language Studies, 2026)
The article is devoted to highlighting the leading problems of the hermeneutic study of an artistic work from a new perspective today.